(untitled) (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1977-79) Chief Editor - M. SHAMIMJAIRAJPURI, Zoology Deptt., A. M. U., Aligarh Editor - E. KHAN, Nematology Divn., 1. A. R. 1., New Delhi Members - A. R. SESHADRI, P. G. School, 1. A. R. 1., New Delhi - K. C. SANWAL, N. B. P. G. R., New Delhi - KISHAN SINGH, 1. 1. S. R., Lucknow - S. N. DAS, Nematology Deptt., O. U. A. T., Bhubaneswar - S. K. SAXENA, Botany Deptt., A. M. U., Aligarh